Nanopartículas de poli-hidroxibutirato-co-valerato como suporte para a imobilização da lipase de Candida antarctica fração B - Fernandes,Ilizandra A.; Nyari,Nádia L. D.; Oliveira,José Vladimir de; Rigo,Elisandra; Souza,Maria Cristiane M. de; Gonçalves,Luciana R. B.; Pergher,Sibele Berenice C.; Oliveira,Débora de (Sociedade Brasileira de Química, 2014)
This work evaluates the immobilization of Candida antarctica lipase (Fraction B) using poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) nanoparticles as support. The effects of immobilization time (30-150 min) and pH (5-10) on lipase loading were evaluated. The stability of the immobilized enzyme towards temperature (40, 60, and 80 ºC), reuse and storage (at 4 ºC) were also determined. Furthermore, to assess its potential application in a system of interest, the immobilized lipase was used as a catalyst in the esterification of geraniol with oleic acid. The results indicated a time of 120 minutes and pH of 7 as optimal for immobilization. A 21 hour exposure of the PHBV-lipase derivative to 60 ºC showed a 33% reduction of the initial activity while storage at 4 ºC led to a residual activity (5% of the original activity). The derivative was used without significant loss of activity for 4 successive cycles. The use of the immobilized lipase as a catalyst in the production of geranyl oleate led to about 88% conversion of the initial reactants to products.